Informal Education of Youth and Inclusive Environment - Kravale, Marite; Guseva, Vija (Acta Paedagogica Vilnensia, 2006)
Changes in the social environment, in individual and societal behaviour, in family relationships and job market have also transformed youth perception about the variety. It is essential to study the experience and the attitude of youth to help them to develop mare tolerant attitude towards the otherness and to foster understanding among people. The aim of the article is to study the attitude of youth towards people with special needs. This leads to a conclusion that it is essential to develop societal opinion about the otherness.